Prime editing optimized RTT permits the correction of the c.8713C>T mutation in DMD gene - Cedric Happi Mbakam; Joel Rousseau; Yaoyao Lu; Anne Bigot; Kamel Mamchaoui; Vincent Mouly; Jacques P. Tremblay (Elsevier, 2022)
Duchenne muscular dystrophy is a severe debilitating genetic disease caused by different mutations in the DMD gene leading to the absence of dystrophin protein under the sarcolemma. We used CRISPR-Cas9 prime editing technology for correction of the c.8713C>T mutation in the DMD gene and tested different variations of reverse transcription template (RTT) sequences. We increased by 3.8-fold the editing percentage of the target nucleotide located at +13. A modification of the protospacer adjacent motif sequence (located at +6) and a silent mutation (located at +9) were also simultaneously added to the target sequence modification. We observed significant differences in editing efficiency in interconversion of different nucleotides and the distance between the target, the nicking site, and the additional mutations. We achieved 22% modifications in myoblasts of a DMD patient, which led to dystrophin expression detected by western blot in the myotubes that they formed. RTT optimization permitted us to improve the prime editing of a point mutation located at +13 nucleotides from the nick site to restore dystrophin protein.